Albert the Great's refutation against the extranission theory of vision through the extramission theory of relection - Saparmin, Norzakiah (Tamhidi Centre, Universiti Sains Islam Malaysia, 2016)
Albert the Great (d.1280 CE) or Albertus Magnus was the founder of Christian Aristotelianism, the medieval scholastic venture which reached its culmination in the teachings of his student, Thomas Aquinas (d.1274 CE). His writings reflect his effort in synthesizing Aristotelian philosophy with Christian teachings, and for this paper we would focus on chapter eighth of his work of De sensu et sensato (Sense and Sensibilia), which is entitled “A Digression to Destroy this Error by Considering the Consequences of Their Statements.” The whole treatise of De sensu delineates Albert’s refutation against extramission theory of vision in his task of introducing and establishing Aristotelian intromission theory in the medieval scholastic scholarship. Thus the chapter eighth focuses on Albert’s claim on the absurdities of the extramission theory by refuting on the extramision theory of reflection. We will delineate further what does this theory mean, and the arguments brought forward by Albert against this theory in this particular chapter. Our methodology is a literature review of which we would review also the extramission theory of vision of Plato and Empedocles, the most important proponents of this theory in Greek philosophy, and the intromission theory of Ibn Haytham (d.1040 CE), who was the first scholar to establish scientific evidence of intromission theory. We would later discover that Albert has five major objections against the extramission theory of reflection, and most of his arguments are in the form of reductio ad absurdum, on which he tried to show that all the premises of the extramission theory of reflection, either explicitly derived or implicitly deduced from the theory would only lead to an absurdity or a contradiction of the conclusion.